Testing the Magnetar Model via Late-Time Radio Observations of Two Macronova Candidates - Horesh, A.; Hotokezaka, K.; Piran, T.; Nakar, E.; Hancock, Paul (Institute of Physics Publishing, 2016)
Compact binary mergers may have already been observed as they are the leading model for short gamma-ray bursts (sGRBs). Radioactive decay within the ejecta from these mergers is expected to produce an infrared flare, dubbed macronova (or kilonova), on a timescale of a week. Recently, two such macronova candidates were identified in followup observations of sGRBs, strengthening the possibility that those indeed arise from mergers. The same ejecta will also produce long-term (months to years) radio emission due to its interaction with the surrounding interstellar medium. In the search for this emission, we observed the two macronova candidates, GRB 130603B and GRB 060614, with the Jansky Very Large Array (VLA) and the Australia Telescope Compact Array (ATCA). Our observations resulted in null-detections, putting strong upper limits on the kinetic energy and mass of the ejecta. A possible outcome of a merger is a highly magnetized neutron star (a magnetar), which has been suggested as the central engine for GRBs. Such a magnetar will deposit a significant fraction of its energy into the ejecta leading to a brighter radio flare. Our results, therefore, rule out magnetars in these two events.